Crosstalk between the developing pancreas and its blood vessels: an evolving dialogue - Villasenor, Alethia (Semin Cell Dev Biol, 2012)
Growth and development of embryonic organs goes hand in hand with development of the vascular system. Blood vessels have been known for centuries to supply nutrients and oxygen to all cell types in an organism, however, they have more recently been shown to provide specific cues required for the formation and functionality of a number of tissues. Here, we review the role of blood vessels during pancreas formation, from early specification of the initial pancreatic bud, to its growth and maturation. The overarching theme that emerges from the many studies carried out in the past decade is that the vasculature likely plays diverse and changing roles during pancreas organogenesis. Blood vessels are required for endocrine specification at the onset of pancreatic budding, while only a few days later, blood vessels suppress pancreatic branching and exocrine differentiation. In this review, we summarize our understanding to date about the crosstalk between the pancreas and its vasculature, and we provide a perspective on the promises and challenges of the field.